CHAOSKAMPF IN THE ORTHODOX BAPTISM RITUAL - Constantin Oancea (Acta Theologica)
The present article analyses the occurrence of the Chaoskampf motif in the Orthodox Baptism ritual and its biblical and Near-Eastern backgrounds. Such statements are direct references to Old and New Testament texts in which water has negative connotations, being associated with hostile or chaotic aspects of existence. In the baptismal interpretation of the biblical motif, sea, depths and dragons are figurative names for demons. The liturgical reinterpretation of these biblical references is the preamble of the baptismal exorcisms. Biblical texts about the struggle against chaos were included in the ritual in order to illustrate Christ’s supremacy over all hostile forces subduing man before Baptism. This illustrative process occurred with the historical development of the baptism ritual after the 4th century.